Current achievements in modifying crop genes using CRISPR/Cas system - A. M. Korotkova; S. V. Gerasimova; E. K. Khlestkina (Вавиловский журнал генетики и селекции)
With the advent of the new genome editing tool of target-specifically customizable endonucleases, a huge variety of novel opportunities have become feasible. The crop improvement is one of the main applications of genome editing in plant science and plant biotechnology. The amount of publications referring to genome editing and CRISPR/Cas system based molecular tools application in crops is permanently growing. The aim of this study is the systematization and cataloging of these data. Earlier we published the first catalog of targeted crop genome modifications as of February 10, 2017. The current review is an update of the catalog; it covers research papers on crop genome modifications from February 10, 2017 to August 17, 2018, found by searching 47 crop names in the Scopus database. Over one year and a half, 377 articles mentioning CRISPR/Cas and crop names have been published, of which 131 articles describe an experimental application of this tool for editing 193 genes in 19 crops, including rice with the largest number of genes modified (109 genes). Editing 50 of 193 genes was aimed at crop improvement. The catalog presented here includes these 50 genes, specifying the cultivars, each gene and gene product function, modification type and delivery method used. The current full list of genes modified with CRISPR/Cas with the aim of crop improvement is 81 in 16 crops (for 5 years from August 2013 to August 2018). In this paper, we also summarize data on different modifications types in different crops and provide a brief review of some novel methods and approaches that have appeared in crop genome editing research over the reviewed period. Taken together, these data provide a clear view on current progress in crop genome modifications and traits improvement using CRISPR/Cas based genome editing technology.